Ribavirin-induced down-regulation of CCAAT/enhancer-binding protein α leads to suppression of lipogenesis. Issue 1 (15th January 2019) - Satoh, Shinya; Onomura, Daichi; Ueda, Youki; Dansako, Hiromichi; Honda, Masao; Kaneko, Shuichi; Kato, Nobuyuki
Abstract : Recently, we demonstrated that the anti-viral drug ribavirin (RBV) had the ability to suppress lipogenesis through down-regulation of retinoid X receptor α (RXRα) under the control of the intracellular GTP-level and AMP-activated protein kinase-related kinases, especially microtubule affinity regulating kinase 4 (MARK4). RXRα-overexpression attenuated but did not abolish lipogenesis suppression by RBV, implying that additional factor(s) were involved in this suppressive effect. In the present study, we found that the protein level, but not the mRNA level, of CCAAT/enhancer-binding protein α (C/EBPα) was down-regulated by RBV in hepatic cells. Treatment with proteasome inhibitor attenuated RBV-induced down-regulation of C/EBPα, suggesting that RBV promoted degradation of C/EBPα protein via the ubiquitin–proteasome pathway. Depletion of intracellular GTP through inosine monophosphate dehydrogenase inhibition by RBV led to down-regulation of C/EBPα. In contrast, down-regulation of C/EBPα by RBV was independent of RXRα and MARK4. Knockdown of C/EBPα reduced the intracellular neutral lipid levels and the expression of genes related to the triglyceride (TG) synthesis pathway, especially glycerol-3-phosphate acyltransferase, mitochondrial ( GPAM ), which encodes the first rate-limiting TG enzyme. Overexpression of C/EBPα yielded the opposite results. We also observed that RBV decreased GPAM expression. Moreover, overexpression of GPAM attenuated RBV-induced reduction in the intracellular neutral lipid levels. These data suggest that down-regulation of C/EBPα by RBV leads to the reduction in GPAM expression, which contributes to the suppression of lipogenesis. Our findings about the mechanism of RBV action in lipogenesis suppression will provide new insights for therapy against the active lipogenesis involved in hepatic steatosis and hepatocellular carcinomas.